Detection and prevention measures for cyberbullying and online grooming - Upadhyay, Aishwarya; Chaudhari, Akshay; Arunesh; Ghale, Sarita; Pawar, S. S. (2017 International Conference on Inventive Systems and Control (ICISC), 2017)
From the day internet came into existence, the era of social networking sprouted. In the beginning, no one may have thought internet would be a host of numerous amazing services like the social networking. Today we can say that online applications and social networking websites have become a non separable part of one's life. Many people from diverse age groups spend hours daily on such websites. Despite the fact that people are emotionally connected together through social media, these facilities bring along big threats with them such as cyber attacks, which includes online grooming and cyberbullying. The primary objective of this project is to detect such cases over the social media and implement some preventive measures so as to avoid such incidents. Using machine learning and data mining techniques we can achieve our goal. The watchdog application could find out the unexpected, unpleasant and unwanted content that could be abusive-disrespectful text or nude images or unpermitted actions and help user removing it or preventing it from being spread all over. This will help the public to assure safety and nonviolence.